Zoraya de daniel samper ortega: la vida amoros a de josé de solís (2000)
LapublicacióndeZorayaen1931seunealaaparicióndeunaseriedeobrasenlanarrativacolombianaenladécad¡1delostreinta,quecompartenunainquietudporbhistoriarporlosproblemassociales;entreellasestánE/estudialiledelamesaredondadeGermán.Arciniegas(1932),ToádeCésarCribePiedrahíta(1933)RiJaraldadeBernardo,\rhsTrujillo(1935),yI..a and lt;'OJedJadeJoséAOsorioLizarazo(1935).Estasobras,ademásdelahistoria,tocantemascomolosdelaparticipacióndelajmentudenloscambiospoliticosysociales,lasituacióndeloscaucherosenlaregiónamazónica,losproblemassocialesdeblancos~negros,ydtferentesaspectosagradablesydesagradablesdela,·idabogotana.ZOI'!J'aeslaúltimadelasnm·elasescritasporelprosistabogotano,guíenteníacomopreocupacionesimportantesensuvida,laedncaciónddpuebloyladi,·ulgacióndelaculturanacional.DanielSamperOrtega(Bogotá,1895)publicólagranmayoríadesusnO\elas,Entrelaniebla.l..JtnmrqtmadeJ#a11doque,1~11elcere:;pl.!...oOlm.rió11y1'MadeBochü and lt;t,entre1923}1928.LaseriedeensayosAlGalopey7.orq_yafueronpublicadosen1930~1931,respectiYamentc.